DEVELOPMENT OF AMMONIA GAS SENSOR BASED ON QUART CRYSTAL MICROBALANCE - Katriani, Laila (Jurnal Sains Dasar, 2024)
Ammonia gas sensor was developed and analyzed using a Quartz Crystal Microbalance (QCM) coated with Polyvinyl Acetate (PVAc) that was overlied by Chitosan. The fabrication process included the electrospinning method to produce nanofiber PVAc on the surface of a QCM. The chitosan solution was diluted to concentrations of 0.1, 0.2, and 0.3 wt%. Subsequently, the chitosan deposition was performed using the drop casting technique on QCM-PVAc. The QCM-PVAc/Chitosan 0.3% composite exhibits a sensitivity of 1.7 Hz ppm-1. Additionally, it demonstrates a linearity of 0.99 within the concentration range of 50 to 500 ppm. In the present study, the limit of detection (LOD) and limit of quantitation (LOQ) were determined to be 0,94 ppm and 2,86 ppm, respectively. The response time of the system was measured to be 7 seconds, indicating a relatively quick detection capability. Furthermore, the sensor exhibited stability during the course of the experiment. Notably, it demonstrated high selectivity towards ethanol, toluene, methanol, acetone, and water molecules. The incorporation of chitosan by drop casting has resulted in enhanced selectivity and sensitivity of the sensor.bstract in English.